Determinant Affecting Blood Sugar, Cholesterol and Uric Acid Levels in Women of Childbearing Age - Rohmawati, Indah; Saripah, Anna Sapti; Setiawan, Aris; Krisdyana, Bekti; Ningtiyasari, Nunik; Ismail, Mohammad (RRZ Scientific Publishing, 2025)
The incidence of metabolic disorders in women of childbearing age in Indonesia, especially those related to blood sugar levels, cholesterol levels, and uric acid levels, continues to increase. Therefore, it is necessary to identify several causal factors. This study aimed to determine the variables related to blood sugar, cholesterol, and uric acid levels. The types of research were observational, analytic, and cross-sectional. The study population consisted of female Tulungagung employees in the Health Office, with purposive sampling obtained 41 respondents. Inclusion criteria: aged 19-49 years, participating in Posbindu activities held at the Health Office in November 2024. This study was conducted at the Tulungagung Regency Health Office in November 2024. Data was collected by measuring height, weight, waist circumference, blood sugar, uric acid, and cholesterol levels, using a microtoise, weight scales, metline, and Easy Touch GCU. Data were analyzed using multiple linear regression testsThe result this study, age had been shown to have an effect on blood sugar levels, and both body mass index (BMI) and excess body weight have been shown to increase uric acid levels. The BMI and weight are both within the normal range, and leading a healthy lifestyle can help prevent difficulties that are caused by metabolic disorders.